PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, OBJEKTIVITAS, INTEGRITAS DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT - Wardana, Made Aris; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
This research was conducted in order to know, analyze and obtain empirical evidence about the influence of transformational leadership style, objectivity, integrity, and ethical auditors on audit quality possessed auditor in public accounting firm Denpasar. The study population was all auditors working in Public Accounting Firm (KAP) and registered in the Directory IAPI in Denpasar, Bali. The method used is saturated sampling method, with a total of 75 respondents with a return rate (responder rate) of 100%. Data analysis techniques used in this study multiple linear regression analysis. Results of the analysis concluded that the transformational leadership style significant positive effect on audit quality, objectivity significant positive effect on audit quality, integrity significant positive effect on audit quality and auditor ethics significant positive effect on audit quality.
Keywords: Transformational Leadership Style, Objectivity, Integrity, Ethics Auditor, Quality Audit